A study of the impact of data intelligence on software delivery performance - DONG, Yongdong (Institutional Knowledge at Singapore Management University, 2023)
With the rise of big data and artificial intelligence, data intelligence has gradually become the focus of academia and industry. Data intelligence has two obvious characteristics: big data drive and application scene drive. More and more enterprises extract valuable patterns contained in data with prediction and decision analysis methods and technologies such as large-scale data mining, machine learning and deep learning and use them to improve the management and decision in complex practice, so as to promote changes of new business modes, organizational structures and even business strategies, and improve the operational efficiency of organizations. However, there are few studies on how data intelligence affects organizational performance. This dissertation points out three-dimensional elements for data intelligence to achieve iterative development: data, technology and prediction and decision-making capability, and makes a more in-depth exploration on the research and application of the three elements and organizational performance. Based on the relevant data of software enterprises, the author conducted empirical research and finally concluded the mechanism and path of data intelligence affecting the software delivery performance, providing an important reference for other industry organizations to improve the operational efficiency and organizational performance.